Critical Analysis of the Development of Surabaya Waterfront Coastal Area in Relation to the State’s Right to Control - Jose Andreawan, Jose Andreawan; Martin Roestamy (DE'RECHTSSTAAT, 2025)
In principle, our constitution has regulated the State’s Right to Control as reflected in the constitutional authority given to the state to regulate, manage, oversee, and control all natural resources or branches of production which are crucial for the state and affect the livelihoods of the people. Land acquisition by the Government for the implementation of the national strategic projects often encounters resistance from local communities. This resistance is not baseless, as there are losses suffered by local communities in the execution of these projects. The research applied normative legal research as the method, focusing solely on document studies, with sources of law including legislation, court decisions, contracts/agreements, legal theories, and opinions of legal scholars. The suggested solution is that land use by the Government must apply the principle of caution to prevent land degradation that could lead to natural disasters due to the construction of the Surabaya waterfront. Essentially, the state’s right to control should not be interpreted as the state’s absolute right to individually control all natural resources. Instead, its meaning is limited to actions taken by the Government in managing natural resources that must aim for the greatest welfare of the people.